Keaktifan Siswa pada Organisasi Siswa Intra Sekolah Terhadap Prestasi Belajar Siswa di SMA Negeri 3 Bulukumba - Ira wahyuni; Abdul Rijal; Samsinar (Program Studi Pendidikan Akuntansi, Fakultas Ekonomi, Universitas Negeri Makassar, 2023)
This research aimed to determine the effect of student activity in intra-school student organizations on student achievement at SMA Negeri 3 Bulukumba ini the 2021/2022 academic year. The variables in this study are (1) student activity in intra-school student organizations as the independent variable (X), and (2) learning achievement as the dependent variable (Y). The population in this study are all students of the MPK/OSIS management at SMA Negeri 3 Bulukumba, totaling 36 students. The sampling technique used was the saturated sample technique, all members of the population were used as samples, namely 36 students. Data collection techniques used are questionnaires and documentation. The data analysis technique used is instrument test, classical assumption test, and hypothesis testing. The instrument test consists of a validity test and a reliability test. Classical assumption test consists of normality test, heteroscedasticity test, and linearity test. The hypothesis test consists of simple linear regression, t-test, and coefficient of determination (r²). Based on the results of descriptive analysis, student activity in intra-school student organizations is in the very good category and learning achievement is in the good category. From the results of simple linear regression analysis, the equation Y = 50.014 + 0.541 X, which means that for every 1 additional student activity value in intra-school student organizations, the learning achievement value has increased by 0.541 units. Meanwhile, from the t-test results obtained a significant value of 0.000 <0.05 percent, which means that student activity in intra-school student organizations has a positive and significant effect on student achievement, thus the hypothesis is accepted. Meanwhile, from the analysis of the coefficient of determination (r²) the value of r² = 0.770 or 77 percent means that student activity in intra-school student organizations has an influence on student achievement by 77 percent while the remaining 23 percent is influenced by other factors.